Effect of feeding different levels of duckweed on the growth of Nepalese Boer-cross goat (Journal of the Bangladesh Agricultural University, 2026)
The experiment was conducted to determine the feed intake and body weight (BW) change of Boer cross buck supplemented with a commercial concentrate mass and combinations of commercial concentrate (CF) with duckweed (Lemna minor) at varying inclusion levels at Goat Research Farm of the Directorate of Agricultural Research (DoAR), Khajura, Banke District, under Nepal Agricultural Research Council (NARC) Nepal for 90 days (2024/25).  In the experiment sixteen healthy bucks 6-7 months old with an average initial body weight 14.43 kg were randomly allocated to four dietary treatments:100% CF+ 0% duckweed (T0), 90 % CF + 10% duckweed (T₁), 80% CF + 20% duckweed (T₂), and 70% CF + 30 % duckweed (T₃), with ad libitum Napier grass provided across all groups. The results reveled that, significant (p